Potret Kultur Perempuan Pesantren Serta Implikasi Kepemimpinannya dalam Novel Hati Suhita Karya Khilma Anis - Mayada, Mayada; Supratno, Haris; Raharjo, Resdianto Permata (Jurnal Riset Rumpun Ilmu Bahasa, 2024)
Literature is an inseparable part of the surrounding reality, presented in the form of fiction. Women are consistently included as objects that provide a unique symbol in conveying its implied messages. Similarly, within the pesantren (Islamic boarding school) environment, women possess their own distinct culture that conforms to the habits that bind them. This portrayal is depicted in the literary work, the novel Hati Suhita by Khilma Anis. The pesantren woman is described concerning her tendencies in pesantren life and her role as the successor in the leadership relay within it. This research aims to describe (a) the portrayal of the pesantren woman's culture in the novel Hati Suhita by Khilma Anis, and (b) the implication of the pesantren woman's leadership on the development of the pesantren in the novel Hati Suhita by Ning Khilma Anis. The approach in this study uses a qualitative methodology. The data source for this research is the novel Hati Suhita by Khilma Anis. The data in this study consist of findings relevant to the problem focus within the novel Hati Suhita by Khilma Anis. The data collection technique used is literature study The data analysis technique used is descriptive qualitative. The results obtained are: The pesantren woman described in the novel Hati Suhita by Khilma Anis is portrayed with the attitudes of obedience and humility as the defining characteristics of a santri (pesantren student). The novel Hati Suhita lays out the implication of her leadership, which brings advancement and renewal to her in-laws' pesantren.